ANALISIS PENGARUH PROMOSI ONLINE TERHADAP PENJUALAN PRODUK PT PARAGON TECNOLOGY AND ENOVATION - Andini, Septiyana; Rahmadani, Suci; Pratiwi, Yunisa Dwi; Anggraini, Riska; Putri, Marcella Wijaya (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract : This research analyzes the influence of online promotions on PT product sales. Paragon Technology and Innovation, producer of beauty brands such as Wardah, amidst the rapid growth of the Indonesian beauty industry. Using the linear regression method, this research identifies the main factors that influence consumer behavior and provides strategic recommendations for companies in designing more effective digital marketing campaigns. The research results show that online promotions have a significant influence on PT product sales. Paragon, but the variable "the influence of online promotions on sales of PT Paragon products" does not have a significant effect. This research recommends improving online promotional strategies and further research to identify other factors that may influence sales. Keywords: Online Promotion, Sales, PT. Paragon Technology and Innovation, Linear Regression, Beauty Industry, Digital Marketing, Buying Interest, Influencer Marketing.